UJI AKTIVITAS PENGHAMBATAN ENZIM SANTIN OKSIDASE OLEH EKSTRAK AIR BEBERAPA JENIS TUMBUHAN SUKU ASTERACEAE DAN ANNONACEAE - Kesturi R, Zahra
Gout is a metabolic disease characterized by recurrent episodes of acute arthritis due to deposits of monosodium urate in joints and cartilage. Xanthine oxidase is an enzyme that plays a role in catalyzing the oxidation of hypoxanthine to xanthine and then to uric acid. In Indonesia, some plants belonging to Asteraceae and Annonaceae families traditionally used to treat the symptoms of hyperuricemia. This study aimed to verify the efficacy of the selected plants through the xanthine oxidase inhibitory activity. The xanthine oxidase inhibitory activity was assayed from 14 species belonging to the families of Asteraceae and Annonaceae used traditionally as therapy for gout. The inhibition of xanthine oxidase enzyme was determined by a decrease in the absorbance of uric acid measured by UV-VIS spectrophotometer at a wavelength of 295 nm. The IC50 value was determined on a extract that had the strongest xanthine oxidase inhibitory activity at a concentration of 100 ?ã???. All of the water exctracts showed to have xanthine oxidase inhibitory effect ranging from 15-???¬?????ã???®??®±???¬?ð???í± ?¬?±?±???¬®??» ®í???¬??í±???»???±??Chrysanthemum morifolium Ramat.) exhibited the strongest activity with an inhibition of 59.76±0.95 (%) and IC50 value 41.02 ?ã????í± =????50 value of allopurinol which used as a positive control was 0.???ã???? This study showed that some plants of Asteraceae and Annonaceae that are used traditionally have inhibitory activity of xanthine oxidase.